L’ordine delle tavole del Liber Figurarum: alcune ipotesi sui codici di Reggio Emilia e Oxford - Rainini, Marco (Annali di scienze religiose, 2012)
The present contribution takes into consideration the problem of the sequence of the different bookplates of the «Liber Figurarum», the collection of the diagrams by Joachim da Fiore especially witnessed to by four manuscripts. Because each witness offers a different disposition of the figures which build it up, the question arises about the original order of the bookplates in their hypothetical archetype, and even of its nature. The present contribution first of all verifies the four different dispositions, and that one - on its turn also different - offered in its first edition, edited by Leone Tondelli, Marjorie Reeves and Beatrice Hirsch-Reich. On the basis of some more recent acquisition, in favor of the witness kept in Reggio Emilia which has to be considered a direct copy of that more ancient and important one kept at Oxford, an in-depth cross examination is operated between the two, and so one may come to hypothesize their original disposition.